Religious moderation campaign: Student forms and strategies to build harmonization on social media - Rosyida Nurul Anwar (Universitas Negeri Yogyakarta, 2023)
The increasing use of social media due to the development of technology and information gives rise to the influence of religious communication on social media. The use of social media is used for dogmatic interests, especially on issues related to the cultivation of certain religious concepts. The view of exclusivity that arises from the boundaries of the digital space is increasingly fertile with the scarcity of moderate Islamic symbols in the digital area. Moderation campaigns need to be carried out, one of which is through social media to establish harmony between religious communities. This study aims to determine how the shape and strategy of Muslim students in public universities in the city of Madiun. This research uses a qualitative descriptive type. The research method is through observation, interviews, and documentation. Data analysis techniques using Milles and Huberman and the validity of the data in the study using data triangulation. The results showed that the forms and strategies of student campaigns are: first, students build religious harmonization through status postings in the form of photos and videos on their social media; both students tried to stop posts that caused division and debate by not sharing. Third, students confirm the dissemination of information that is considered inappropriate through question and answer and discussion. Fourth is the creation of short-duration animated images for distribution. Harmonization in religion is an effort to create peace in every aspect of life.